The effects of wave activity on overtopping and scouring on a vertical breakwater - Mustafa, Mamat; Novan, Tofany; Mohammad Fadhli, Ahmad (2016)
A numerical study is presented herein to investigate the effects of wave activity on overtopping discharges and scouring offshore of a vertical breakwater. A 2D RANS-VOF model was used to study this topic. The model was coupled with turbulence closure, sediment transport, and morphological models with additional bottom shear stresses in the momentum equations. Validation results show that the numerical predictions of velocities are in good agreement with the experimental data and the analytical solution. The predicted scour patterns and maximum equilibrium scour depths also show better accuracy than the results of existing models. Numerical experiments were then conducted by varying wave and breakwater height (freeboard) which result in different overtopping discharges. The effects of different wave heights and freeboards on the overtopping discharge, and the subsequent effects on the hydrodynamics and scouring were analyzed. The results of this analysis will be discussed in details in this paper and are expected to be worthwhile in the process of designing breakwater in coastal areas.